2013
DOI: 10.1097/mib.0b013e31829936c2
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Reduces Hospitalizations and Surgery Interventions in Patients With Inflammatory Bowel Disease

Abstract: The best evidence available points toward a reduction of the risk of hospitalization and major surgery requirement in patients with IBD treated with infliximab. This impact is clinically and economically relevant because hospitalization and surgery are considered to be markers of disease severity and significantly contribute to the total direct costs associated with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 66 publications
(110 reference statements)
2
62
2
2
Order By: Relevance
“…Compared to cohort A, cohort B had more patients on immunomodulators (cohort A vs cohort B: 21.4% vs 56.1%, P < 0.0001) and less patients on 5-aminosalysilic acid (53.6% vs 29.8%, P = 0.001). There was a shift from inflammatory to stricturing and penetrating phenotypes (B1/B2/B3 38.8% vs 12.3%, 31.8% vs 45.6%, 29.4% vs 42.1%, P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to cohort A, cohort B had more patients on immunomodulators (cohort A vs cohort B: 21.4% vs 56.1%, P < 0.0001) and less patients on 5-aminosalysilic acid (53.6% vs 29.8%, P = 0.001). There was a shift from inflammatory to stricturing and penetrating phenotypes (B1/B2/B3 38.8% vs 12.3%, 31.8% vs 45.6%, 29.4% vs 42.1%, P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis showed infliximab reduces hospitalization and major surgery [29] . Our study found that anti-TNF agents and combination therapy extend time from CD disease diagnosis to first surgical resection in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Biological therapy such as Infliximab has been demonstrated to reduce the risk of hospitalisation and need for surgery in UC. 31 However, personal experience as well as the results from the national IBD audit indicate use of rescue therapy to have been low in Scotland during study Period 2: of 26 UC patients who did not respond to steroid, only four received infliximab (75% of whom responded) and none received ciclosporin during the audit period. 3 Overall, the uptake of rescue therapy and biological treatments in Scotland in the 2010 UK IBD Audit was less than 5% in severe UC, compared with over 20% elsewhere in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent meta-analysis, Costa et al [34] analyzed the association between IFX therapy and hospitalization risk. Twenty-seven studies (9 RCT and 18 observational studies) were included.…”
Section: Efficacy Beyond Clinical Remission: Hospitalization Surgerymentioning
confidence: 99%